Yémen : le Sud sur la voie de la sécession ? - Franck Mermier (EchoGéo)
Since Yemen's internal war of 1994, the growing resentment of the populations of the South towards the power stronghold of Sanaa has been aggravated by a severe economic crisis, a galloping inflation and a high rate of unemployment. All of which have contributed to a situation of social despair that is now fertile grounds for separatist or federalist claims.